A low-carbon mass concrete and preparation method thereof
By using aggregate selection, mix ratio optimization and heat storage particles in the preparation of large volume concrete, the problems of high carbon emissions and early cracking of large volume concrete are solved, and low carbon, high strength and strong durability are achieved. Concrete production.
Patent Information
- Application Number
- CN202310938078.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-28
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-07-28
AI Technical Summary
During the production of large-volume concrete, high carbon emissions, resource waste and early cracking are serious, resulting in poor environmental pollution and engineering quality.
The preparation method of low-carbon large volume concrete is adopted, and the use of fly ash and cement is reduced, CO2 emissions are reduced, temperature stress is controlled, and the strength and durability of concrete are improved through aggregate selection, mix ratio optimization and heat storage particles. .
Generate low-carbon large-volume concrete with good construction performance, high strength, strong durability and not easy to crack, which significantly reduces carbon emissions and production costs, and has significant economic benefits and environmental protection value.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and particularly relates to a low-carbon mass concrete and a preparation method thereof. Background Art
[0002] The concrete manufacturing process involves the use of a large amount of cement, and the cement production process is one of the links with high energy consumption and high carbon emissions. Mass concrete is widely used in large projects such as bridges, tunnels, and high-rise buildings due to its high strength, good durability, high construction efficiency, and earthquake resistance. However, the production of mass concrete consumes a huge amount of raw materials such as cement and aggregates, the construction technology is complex, and temperature stress cracks are prone to occur. In addition, a large amount of carbon dioxide and other pollutants will be generated during transportation and construction. The average carbon emission of a single cubic meter of concrete reaches 312kg / m 3 , an average of 56 million tons of construction waste is generated each year, which not only wastes a large amount of natural resources, but also causes serious environmental, noise and dust pollution.
[0003] In recent years, the use of mineral admixtures in large-volume concrete has greatly reduced the amount of cement used. However, the addition of silica fume, fly ash and ground slag has promoted the formation of shrinkage cracks in concrete. Secondly, in terms of design and construction, higher requirements are placed on the working performance of concrete. The amount of cement used has gradually increased, and the requirements for slump and expansion have also increased simultaneously. These requirements have further increased the shrinkage of concrete. At the same time, in terms of maintenance, some complex cast-in-place structures are not conducive to thermal insulation and moisture maintenance of concrete, which increases the risk factors for cracks in large-volume box girder concrete. At the same time, due to the shortage of natural sand, the quality of aggregates is uneven. These factors cause large-volume concrete to easily crack early, resulting in a waste of resources, an increase in carbon dioxide emissions, and an increase in the pressure to reduce emissions. Summary of the invention
[0004] The present invention aims to provide a low-carbon mass concrete and a preparation method thereof, which adopts direct and indirect carbon reduction technologies, reduces the amount of fly ash and cement in concrete through aggregate selection, mix ratio optimization, and addition of heat storage particles, thereby reducing CO 2 It reduces emissions and the risk of cracking of large-volume concrete due to temperature stress, and produces low-carbon large-volume concrete with good construction performance, high strength, strong durability and not easy to crack, which has considerable economic value and environmental protection benefits in terms of main material costs.
[0005] In order to achieve the above purpose, the technical solutions adopted are as follows:
[0006] A low-carbon mass concrete, the composition by weight is as follows:
[0007] 180-280 parts of cement, 50-80 parts of mineral powder, 40-50 parts of fly ash, 960-1000 parts of crushed stone, 750-850 parts of fully graded machine-made sand, 40-60 parts of heat storage particles, 7-9 parts of admixtures, and 150-160 parts of water.
[0008] In the above scheme, the heat storage particles are prepared in the following manner:
[0009] 1) reacting benzoyl chloride and p-butylphenol in an alkaline environment to prepare a reaction solution A containing a nematic liquid crystal monomer; preparing a crosslinking agent reaction solution B by reacting acrylic acid and butanediol under a strong acid catalyst condition;
[0010] 2) mixing reaction solution A, reaction solution B and polymethylhydrogensiloxane in an organic solvent to obtain a liquid crystal elastomer solution C;
[0011] 3) Immersing the heat storage carrier in the liquid crystal elastomer solution C, heating with microwaves, and drying to constant weight to obtain heat storage particles; the heat storage carrier is perlite particles with a particle size of 1-2 mm and a porosity of 40-50%.
[0012] In the above scheme, the particle grading composition of the fully graded machine-made sand fraction screen residue is as follows: the content of particles with a particle size greater than 4.75 mm is 0-2%, the content of particles with a particle size of 2.36-4.75 mm is 8-14%, the content of particles with a particle size of 1.18-2.36 mm is 18-25%, the content of particles with a particle size of 0.6-1.18 mm is 20-25%, the content of particles with a particle size of 0.3-0.6 mm is 16-19%, the content of particles with a particle size of 0.15-0.3 mm is 10-14%, and the content of particles with a particle size less than 0.15 mm is 13-16%.
[0013] In the above scheme, the fineness modulus of the fully graded machine-made sand is 2.43-2.78, the stone powder content is 9-13%, and the crushing value is 7-10%.
[0014] In the above scheme, the fly ash is of grade II, with an activity index greater than 75%, a mass fraction of fineness passing through a 325-mesh sieve greater than or equal to 70%, a moisture content less than or equal to 3%, a sulfate content less than or equal to 2.0%, and a chloride ion content less than or equal to 0.1%.
[0015] In the above scheme, the mineral powder is S95 mineral powder with a particle size less than 0.045 mm.
[0016] In the above scheme, the cement is ordinary Portland cement with a strength grade of 42.5R or above.
[0017] In the above scheme, the stone is 5-20mm continuously graded crushed stone.
[0018] In the above scheme, the additive is a lipid polycarboxylic acid.
[0019] The present invention also provides a method for preparing low-carbon mass concrete, comprising the following steps:
[0020] 1) Mixing cement, fly ash, mineral powder and fully graded machine-made sand to obtain a first mixture;
[0021] 2) mixing the first mixture, the heat storage particles and the crushed stones to obtain a second mixture;
[0022] 3) Mixing water and admixture, adding them into the second mixture and stirring to obtain the low-carbon mass concrete.
[0023] According to the above scheme, in the method for preparing low-carbon mass concrete, the stirring time of step 1) is 20-30s; the stirring time of step 2) is 20-30s; and the stirring time of step 3) is 160-190s.
[0024] The active Si-H bonds in the liquid crystal monomer of the present invention undergo 100% grafting reaction with all the vinyl groups in the crosslinking agent and polymethylhydrogensiloxane to form a liquid crystal elastomer solution.
[0025] Liquid crystal elastomer has good heat storage performance. After the liquid crystal elastomer solution intrudes into the pores of perlite particles, it is microwave treated and dried to form heat storage particles. The heat storage particles are combined with fully graded machine-made sand, and the carbon reduction and fly ash reduction system mix ratio is designed. The total "inert" powder in the fully graded machine-made sand and fly ash is graded and redistributed to reduce the inert powder content, improve the working performance of the concrete mixture, and reserve filling space for the hydration reaction of the adhesive. The generated hydration products can better adhere to and wrap the aggregate, reduce the amount of fly ash and cement in the concrete, and reduce CO 2 emissions and improve the strength of concrete; during the concrete hardening process, the liquid crystal elastomer in the heat storage particles absorbs the heat of hydration, controls the internal temperature of the large volume concrete, reduces the temperature stress caused by the temperature difference between the surface and the interior of the large volume concrete, and greatly reduces the probability of temperature cracks; the surface of the heat storage particles is rough, which increases the bite force between the aggregates. The rough surface also increases the bonding area with the cement paste, forming a denser structure, which can produce low-carbon large volume concrete with good construction performance, high strength, strong durability, not easy to crack, and low carbon emissions.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] (1) Low-carbon mass concrete prepared by this technology can reduce the amount of fly ash and cement in concrete and reduce CO 2 It can reduce emissions, improve the strength of concrete, reduce production inputs, and reduce carbon emissions, which has significant economic benefits and environmental protection value.
[0028] (2) Low-carbon mass concrete with heat storage particles has a smaller temperature difference between the inside and outside during the hardening process, a lower probability of temperature cracks, reduced maintenance difficulty, and reduced subsequent maintenance costs, which has extremely high engineering application value.
[0029] (3) The research and development background of low-carbon mass concrete mainly includes the pressure on carbon emissions, international commitments and policy advocacy, the need for technological innovation and changes in market demand. The research and development and promotion of low-carbon mass concrete can reduce the negative impact of the construction industry on the environment and achieve sustainable development goals. DETAILED DESCRIPTION
[0030] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.
[0031] In the following examples, ordinary Portland cement with a strength grade of 42.5R or above is selected;
[0032] The selected fully graded machine-made sand has the following particle grading composition: 0-2% of particles with a diameter greater than 4.75 mm, 8-14% of particles with a diameter of 2.36-4.75 mm, 18-25% of particles with a diameter of 1.18-2.36 mm, 20-25% of particles with a diameter of 0.6-1.18 mm, 16-19% of particles with a diameter of 0.3-0.6 mm, 10-14% of particles with a diameter of 0.15-0.3 mm, and 13-16% of particles with a diameter less than 0.15 mm; the fineness modulus of the fully graded machine-made sand is 2.43-2.78, the stone powder content is 9-13%, and the crushing value is 7-10%.
[0033] The fly ash selected is Grade II, with an activity index greater than 75%, a fineness (mass fraction passing a 325-mesh sieve) greater than or equal to 70%, a moisture content less than or equal to 3%, a sulfate content less than or equal to 2.0%, and a chloride ion content less than or equal to 0.1%; the parent rock is carbonate rock salt, and the crushing value is 7-10%.
[0034] The selected crushed stone is 5-20mm continuously graded crushed stone.
[0035] The selected mineral powder is S95 mineral powder with a particle size less than 0.045mm.
[0036] The specific embodiment provides a method for preparing heat storage particles:
[0037] 1) reacting benzoyl chloride and p-butylphenol in a mass ratio of (1-1.5):1 in a 0.5 mol / L NaOH alkaline solution, controlling the temperature at 75±1°C, and reacting for 15 minutes to prepare a reaction solution A containing a nematic liquid crystal monomer p-butylbenzoyloxybenzene; reacting acrylic acid and butanediol in a mass ratio of (1.3-2):1 under concentrated sulfuric acid catalysis, controlling the reaction temperature at 50±2°C, and reacting for 20 minutes to prepare a crosslinking agent reaction solution B;
[0038] 2) mixing reaction solution A, reaction solution B and polymethylhydrogensiloxane in an organic solvent at a mass ratio of 5:2:3 for 30 minutes to obtain a liquid crystal elastomer solution C, and controlling the reaction temperature to 65-70° C.;
[0039] 3) Immersing the heat storage carrier in the liquid crystal elastomer solution C, performing microwave heating treatment, and drying to constant weight to obtain heat storage particles; the heat storage carrier is perlite particles with a particle size of 1-2 mm and a porosity of 40-50%, and the immersion time in the reaction solution C is 0.5-1 h; the microwave power used in the microwave heating treatment is 300-450 kW, the radiation temperature is 25-30° C., and the radiation time is 10-15 min.
[0040] The high-performance fine machine-made sand concrete in Examples 1-4 is composed of cement, mineral powder, fly ash, stone, heat storage particles, fully graded machine-made sand, admixtures, and water. The mass percentage of each component is shown in Table 1.
[0041] Table 1 Composition of high performance fine machine-made sand concrete of Examples 1-4
[0042]
[0043] The preparation method of the dredged sludge composite curing agent in Examples 1-4 comprises the following steps:
[0044] 1) Mixing cement, fly ash, mineral powder and fully graded machine-made sand to obtain a first mixture;
[0045] 2) mixing the first mixture, the heat storage particles and the stone to obtain a second mixture;
[0046] 3) Mixing water and admixture, adding them into the second mixture and stirring to obtain the low-carbon mass concrete.
[0047] Table 2 Main parameters for preparing high-performance fine machine-made sand concrete in Examples 1-4
[0048]
[0049]
[0050] The high-performance fine machine-made sand concrete in Examples 1-4 was subjected to performance tests, the new mixture was subjected to workability tests, and then it was made into test blocks required by the specification for strength and carbonation depth tests. The performance test results are shown in Table 4.
[0051] Table 3 Main parameters of high performance fine machine-made sand concrete application in Examples 1-4
[0052] Example Curing temperature(℃) Curing humidity (%) Curing time (d) Example 1 18 74 7 Example 2 19 75 14 Example 3 20 76 28 Example 4 21 75 14
[0053] Comparative Example 1
[0054] The difference between Comparative Example 1 and Example 4 is that no fully graded machine-made sand is used.
[0055] Comparative Example 2
[0056] The only difference between Comparative Example 2 and Example 4 is that the carbon reduction and fly ash reduction system mix ratio is not used.
[0057] Comparative Example 3
[0058] The only difference between Comparative Example 3 and Example 4 is that concrete is produced without adding heat storage particles.
[0059] Comparative Example 4
[0060] The only difference between Comparative Example 4 and Example 4 is that ordinary machine-made sand and ordinary mix ratio are used, and no heat storage particles are added to produce concrete.
[0061] In order to verify the effects of the above embodiments and comparative examples, the slump, collapse time, and encapsulation of the freshly mixed materials of each embodiment and comparison were tested, and the compressive strength and carbonation depth of the samples after 28 days of curing were tested. Among them, the working performance index was tested for slump and collapse time of freshly mixed concrete according to GB50164-2011 "Concrete Quality Control Standard", and the encapsulation of the mixture was observed and recorded; the compressive strength of the sample after 28 days was tested for unconfined compression according to GB 55008-2021 "General Specification for Concrete Structure"; the carbonation depth of concrete was tested according to T0581-2020 "Test Method for Carbonation of Cement Concrete"; the crack resistance of concrete was evaluated according to "Concrete Durability Inspection and Evaluation Standard" JGJT193-2009. The test results are shown in Table 4.
[0062] Table 4 Test results
[0063]
[0064]
[0065] It can be seen from the data of Examples 1 to 4 that the heat storage particles are combined with a fully graded machine-made sand, the carbon reduction and fly ash reduction system ratio is designed, and the total "inert" powder in the fully graded machine-made sand and fly ash is graded and redistributed, thereby reducing the inert powder content and improving the working performance of the concrete mixture. At the same time, filling space is reserved for the hydration reaction of the adhesive, and the generated hydration product can better adhere to and wrap the aggregate, thereby reducing the amount of fly ash and cement in the concrete and reducing CO. 2 emissions and improve the strength of concrete; during the concrete hardening process, the liquid crystal elastomer in the heat storage particles absorbs the heat of hydration, controls the internal temperature of the large-volume concrete, reduces the temperature stress caused by the temperature difference between the surface and the interior of the large-volume concrete, and greatly reduces the probability of temperature cracks; the surface of the heat storage particles is rough, which increases the bite force between the aggregates. The rough surface also increases the bonding area with the cement paste, forming a denser structure, and producing low-carbon large-volume concrete with good construction performance, high strength, strong durability, not easy to crack, and low carbon emissions.
[0066] It can be seen from the test data of Comparative Example 1 and Example 4 that when ordinary machine-made sand and reduced carbon and fly ash system are used to prepare concrete, the aggregate particle grading is poor, and there is a lack of powder filling, the concrete encapsulation is poor, water seepage occurs, and the bulk strength is low. However, since the components contain heat storage particles, the crack resistance is good.
[0067] It can be seen from the test data of Comparative Example 2 and Example 4 that when concrete is prepared using fully graded machine-made sand, heat storage particles and ordinary mix ratio, the aggregate particles are well graded and a dense skeleton structure is formed, but the amount of fly ash is high, the concrete fluidity is average, the amount of admixtures is high, the strength is low, and the crack resistance is good.
[0068] It can be seen from the test data of Comparative Example 3 and Example 4 that when concrete is produced without using heat storage particles and with a fully graded machine-made sand and a reduced carbon and reduced fly ash system, the aggregate particles are well graded to form a dense skeleton structure, the concrete has good fluidity, and the mass concrete has high strength, but poor crack resistance.
[0069] It can be seen from the test data of Comparative Example 4 and Example 4 that when ordinary machine-made sand and ordinary mix ratio are used to prepare concrete without adding heat storage particles, the aggregate particle grading is poor, the inert powder content is very high, the concrete has poor fluidity and is viscous, the bulk strength is low, and the crack resistance is poor.
[0070] The above embodiments are merely examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above descriptions. It is not necessary and impossible to list all the implementation methods here, and the obvious changes or modifications derived therefrom are still within the protection scope of the invention.
Claims
1. A low-carbon mass concrete, characterized in that The composition is calculated by weight as follows: 180-280 parts of cement, 50-80 parts of mineral powder, 40-50 parts of fly ash, 960-1000 parts of crushed stone, 750-850 parts of fully graded machine-made sand, 40-60 parts of heat storage particles, 7-9 parts of admixtures, and 150-160 parts of water; The heat storage particles are prepared in the following manner: 1) reacting benzoyl chloride and p-butylphenol in an alkaline environment to prepare a reaction solution A containing a nematic liquid crystal monomer; and preparing a crosslinking agent reaction solution B by reacting acrylic acid and butanediol under a strong acid catalyst condition; 2) mixing reaction solution A, reaction solution B and polymethylhydrogensiloxane in an organic solvent to obtain a liquid crystal elastomer solution C; 3) Immersing the heat storage carrier in the liquid crystal elastomer solution C, performing microwave heating treatment, and drying to constant weight to obtain heat storage particles; the heat storage carrier is perlite particles with a particle size of 1-2 mm and a porosity of 40-50%.
2. The low-carbon mass concrete according to claim 1, characterized in that The fineness modulus of the fully graded machine-made sand is 2.43-2.78, the stone powder content is 9-13%, and the crushing value is 7-10%; the grading composition of the residual particles is as follows: the content of particles with a particle size greater than 4.75 mm is 0-2%, the content of particles with a particle size of 2.36-4.75 mm is 8-14%, the content of particles with a particle size of 1.18-2.36 mm is 18-25%, the content of particles with a particle size of 0.6-1.18 mm is 20-25%, the content of particles with a particle size of 0.3-0.6 mm is 16-19%, the content of particles with a particle size of 0.15-0.3 mm is 10-14%, and the content of particles with a particle size less than 0.15 mm is 13-16%.
3. The low-carbon mass concrete according to claim 1, characterized in that The fly ash is of grade II, with an activity index greater than 75%, a mass fraction of fineness passing through a 325-mesh sieve greater than or equal to 70%, a moisture content less than or equal to 3%, a sulfate content less than or equal to 2.0%, and a chloride ion content less than or equal to 0.1%.
4. The low-carbon mass concrete according to claim 1, characterized in that The mineral powder is S95 mineral powder, and the particle size is less than 0.045 mm.
5. The low-carbon mass concrete according to claim 1, characterized in that The cement is ordinary Portland cement with a strength grade of 42.5R or above.
6. The low-carbon mass concrete according to claim 1, characterized in that The crushed stone is 5-20 mm continuously graded crushed stone.
7. The low-carbon mass concrete according to claim 1, characterized in that The additive is lipid polycarboxylic acid.
8. The method for preparing low-carbon mass concrete according to claim 1, characterized in that The following steps are involved: 1) Mixing cement, fly ash, mineral powder and fully graded machine-made sand to obtain a first mixture; 2) mixing the first mixture, the heat storage particles and the crushed stones to obtain a second mixture; 3) Mixing water and admixtures, adding them into the second mixture and stirring to obtain the low-carbon mass concrete.
9. The method for preparing low-carbon mass concrete according to claim 8, characterized in that The stirring time of step 1) is 20-30s; the stirring time of step 2) is 20-30s; and the stirring time of step 3) is 160-190s.
Citation Information
Patent Citations
Anti-crack mass concrete prepared by utilizing fly ash and mineral powder double-mixing technology
CN105948619A
Preparation method of low-temperature-rise mass concrete added with micro-nano heat storage capsules
CN108409208A